Songbooks as a Mode of Personal Notes - Ūsaitytė, Jurgita (Tautosakos darbai, 2015)
The article presents an introductory survey of one variety of the written folklore, namely, the songbooks, which so far have been neither collected nor analyzed in any more consistent manner in the Lithuanian scholarly discourse. However, the two centuries-old tradition of compiling the songbooks calls for discussion of the objective considerations lying behind such disdainful attitude towards them. Certain neglect of the songs rendered in writing resulted from the long-time prevalent notion of folklore as the oral folk creativity. The majority of researchers and folklore collectors considered only those songs that informants performed vocally as truly traditional and authentic; while regarding the texts amassed by the same informants in their personal notebooks as less valuable sources or some rough drafts. Besides, the criteria of value attributed to folklore that was shaped as early as the beginning of the 20th century, encouraged the folklore collectors to search exclusively for the pieces of classical tradition, along with pointing them towards the informants of the elderly generation. Such orientation not only hindered systematic research of the verbal tradition, but also resulted in the tradition of compiling the songbooks, although considerably popular and widespread in the society, to remain essentially unanalyzed and very poorly documented. On the other hand, the absence of methods for collecting the songbooks (as well as other kinds of personal notes) in turn caused the lack of contextual information on their appearing and functioning. This is perhaps the greatest obstacle for carrying out the relevant research of the written folklore. In order to trace back sources of the Lithuanian songbook tradition, the author of the article compares them to other akin forms of the written culture. Songbooks as products of the written culture should doubtless be related to the earlier tradition of the personal writings. The whole paradigm of the personal writings, reaching as far back as the Baroque in Lithuania, comprises miscellaneous sources: diaries, memoirs, autobiographies, silva rerum, letters, albums, notebooks, etc. For instance, some songbooks from the 19th century seem similar to the silva rerum in terms of the miscellaneous contents of both collections, the selection of texts based on the individual logics, and the demand acutely felt by the author / owner to belong to the written culture. Along with considering causes for the increasing number of the songbooks (written in Lithuanian) during the second half of the 19th century, the author also attempts to examine the individual reasons that could have shaped the peculiarity of certain notes, at the same time bearing in mind certain social and historical circumstances. Moreover, detailed analysis of the songbooks compiled in the beginning of the 20th century by a single person – Vincentas Dumčius, allows for grasping intersections of different contexts and for revealing an integral network of cultural and social connections. Description of the formal side of the notebooks (e. g. separation of the headings, numbering of texts, remarks and comments, graphic elements, various inclusions, etc.) demonstrates the ways by which simple structural elements help to create the genre particularity of the writings in question (shaping them as songbooks). It also testifies to the vitality and dynamism of this cultural tradition. Detailed analysis of contents elucidates a special case of the genre contamination, typical not only to the Lithuanian, but also to some other national traditions–namely, the songbook albums. On the basis of experience accumulated while working with the Lithuanian material, as well as relying on the insights by the foreign researchers, several directions for the future investigation are attempted to define that would allow for further interpretation of this form of the written folklore.